2023
DOI: 10.3390/buildings13122912
|View full text |Cite
|
Sign up to set email alerts
|

Views of Cross-Laminated Timber (CLT) Manufacturer Representatives around the World on CLT Practices and Its Future Outlook

Hüseyin Emre Ilgın,
Markku Karjalainen,
Pinja Mikkola

Abstract: Due to its recent emergence, there is a limited body of global market research available on CLT. Presently, the literature lacks comprehensive understanding regarding the present state, varied uses, and future outlook of CLT construction at a global level. The objective of this article is to address this knowledge gap by conducting semi-structured, in-depth interviews with CLT manufacturer representatives around the world, including Austria, Italy, Czech Republic, Sweden, Norway, Finland, Japan, Canada, and Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
2
2
0
Order By: Relevance
“…Incorporating the results of a global study investigating the viewpoints of CLT manufacturers on current practices and future trends would be highly advantageous within the scientific literature [55]. Our study's findings closely aligned with numerous outcomes observed in the investigation by [55].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Incorporating the results of a global study investigating the viewpoints of CLT manufacturers on current practices and future trends would be highly advantageous within the scientific literature [55]. Our study's findings closely aligned with numerous outcomes observed in the investigation by [55].…”
Section: Discussionsupporting
confidence: 72%
“…Incorporating the results of a global study investigating the viewpoints of CLT manufacturers on current practices and future trends would be highly advantageous within the scientific literature [55]. Our study's findings closely aligned with numerous outcomes observed in the investigation by [55]. Echoing our research outcomes, a consensus among global CLT manufacturers underscored a widespread acknowledgment of the knowledge and experience gap concerning CLT among construction industry professionals at large.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Presently, there is a growing interest in expanding the utilization of wood in the construction industry [45][46][47]. Various companies, ranging from large corporations to medium-sized enterprises in the construction sector, are diversifying their focus toward wood construction, indicating a strategic shift in their business approach.…”
Section: Discussionmentioning
confidence: 99%